Attributes of physiotherapy continence clinicians: a qualitative perspective. (March 2020) - Slade, Susan C.; Hay-Smith, Jean; Mastwyk, Sally; Morris, Meg E.; Frawley, Helena
Abstract: Objectives: To understand the attributes of expert physiotherapy continence clinicians and how they compare to novices in relation to experience, knowledge, capability and skills in pelvic floor rehabilitation. Design: Qualitative methods were used for thematic analysis of data collected from clinician focus groups. Participants: Registered physiotherapists in Melbourne, Australia. Recruitment was through purposive, and "snowball" sampling, and continued until attainment of data adequacy. Intervention: Audio recorded focus groups. Results: Twenty-eight physiotherapists participated in seven focus groups. A key finding was that continence rehabilitation is an area of expert physiotherapy practice. Proficiency is often attained through postgraduate education, mentoring by experienced colleagues, clinical experience and research participation. The 'continence clinician as expert' was identified in three main themes (i) attributes that are important for competent continence practice; (ii) research literacy and the ability to generate and translate research into practice; and (iii) patient-centred care, including managing consumer expectations. Knowledge translation was assisted by research literacy, access to evidence and the use of comprehensively reported research. Proficient clinicians prioritised evidence-informed practice, consumer engagement, peer networks and collaboration. Conclusions: The main attributes of proficient physiotherapy continence clinicians were high levels of skill, training and experience, enabling an extended scope of practice. Research capability and research co-partnerships were also seen to support implementation of contemporary, evidence-based practice. Therapists new to this field were thought to benefit from structured mentoring, further training and clear career pathways embedded within healthcare systems. Consumer-focussed care was seen as a core skill across all levels of physiotherapy practice.